Warming effects on permafrost ecosystem carbon fluxes associated with plant nutrients. Issue 11 (25th September 2017) - Li, Fei; Peng, Yunfeng; Natali, Susan M.; Chen, Kelong; Han, Tianfeng; Yang, Guibiao; Ding, Jinzhi; Zhang, Dianye; Wang, Guanqin; Wang, Jun; Yu, Jianchun; Liu, Futing; et al.
Abstract: Large uncertainties exist in carbon (C)‐climate feedback in permafrost regions, partly due to an insufficient understanding of warming effects on nutrient availabilities and their subsequent impacts on vegetation C sequestration. Although a warming climate may promote a substantial release of soil C to the atmosphere, a warming‐induced increase in soil nutrient availability may enhance plant productivity, thus offsetting C loss from microbial respiration. Here, we present evidence that the positive temperature effect on carbon dioxide (CO2 ) fluxes may be weakened by reduced plant nitrogen (N) and phosphorous (P) concentrations in a Tibetan permafrost ecosystem. Although experimental warming initially enhanced ecosystem CO2 uptake, the increased rate disappeared after the period of peak plant growth during the early growing season, even though soil moisture was not a limiting factor in this swamp meadow ecosystem. We observed that warming did not significantly affect soil extractable N or P during the period of peak growth, but decreased both N and P concentrations in the leaves of dominant plant species, likely caused by accelerated plant senescence in the warmed plots. The attenuated warming effect on CO2 assimilation during the late growing season was associated with lowered leaf N and P concentrations. These findings suggest that warming‐mediated nutrient changes may not always benefit ecosystem C uptake in permafrost regions, making our ability to predict the C balance in these warming‐sensitive ecosystems more challenging than previously thought.